O07 National response to an outbreak of hepatitis a associated with men who have sex with men in england, 2016/2017. (8th June 2017) - Edelstein, Michael; Beebeejaun, Kazim; Ngui, Siew Lin; Woodhall, Sarah; Simms, Ian; Crook, Paul; Hughes, Gwenda; Mandal, Sema; Balogun, Koye
Abstract : Introduction: Hepatitis A virus (HAV) is a vaccine-preventable infection, mainly travel-associated in the UK. Since July 2016 Public Health England has detected an increase in hepatitis A laboratory notifications in men who have sex with men (MSM). We described the outbreak characteristics to inform implementation of nation-wide control measures. Methods: A confirmed case was defined as a HAV infection with one of three outbreak strains and symptom onset after 31//6/16. Demographics, travel history and sexual behaviours were collected using a questionnaire. Results: By February 2017, 73 confirmed cases were detected across England. Of these 58 identified as MSM (median age 36 years) and 28 reported travel within the incubation period, primarily to Spain. 25% reported >1 casual partner in the previous 8 weeks. In addition to supporting the local public health response, PHE collaborated with national STI, HIV and liver associations to refine immunisation recommendations for at-risk MSM and alert front-line clinicians, and worked with the NHS and sexual health charities to raise awareness and promote personal hygiene and immunisation among MSM via social media, posters and leaflets. Discussion: The outbreak is likely associated with other MSM outbreaks with the same strains in other UK and European countries. The investigation suggests initial multiple importations from abroad followed by secondary sexual transmission within the MSM population in England. This outbreak highlights the need for MSM and healthcare professionals to consider the potential of HAV as a sexually transmitted infection, and the need to consider immunisation of MSMs where recommended.